Exploring Mental Toughness in NCAA Athletes - Joanne Butt; Robert Weinberg; Briana Culp (University of Kansas Libraries, 2010)
The purpose of the current study was to explore National Collegiate Athletic Association (NCAA) Division 1 athletes' perceptions of mental toughness. Specifically, three areas of mental toughness were explored including attributes, the role of significant others, and strategies used to build mental toughness. In-depth interviews were conducted with 15 athletes from a variety of sports. Lower and higher-order themes were developed to capture the main ideas of mental toughness. Various psychological attributes emerged including performing under pressure, being motivated, being a hard worker, and anticipation. In addition, all athletes referred to coaches as being critical in developing mental toughness (i.e., coaches' support, coaches' attributes, coaches' practices). Creating a positive but tough practice environment emerged as a dominant theme to build mental toughness. In addition, the themes of teaching mental toughness and enhancing athletes' psychological skills emerged. Findings offer implications for aspiring collegiate athletes and their coaches, as well as current NCAA athletes and coaches.